The morning after : a history of emergency contraception in the United States - Prescott, Heather Munro (Critical issues in health and medicine., 2011)
This book is the first to describe the history of emergency contraception from its beginnings in the 1960s. Other historical accounts of this technology focus on the very recent past and present a story of uniform progress from "the nation's best kept secret" to a dedicated product found on most pharmacy shelves.1 In these histories, there are clearly delineated opposing positions: on one side are those who support the technology as an uncomplicated scientific solution to the problem of unwanted pregnancy; on the other are religious conservatives who seek to ban the technology because they erroneously equate it with abortion.